Infertility in practice - Balen, Adam H. (Reproductive medicine and assisted reproductive techniques, 2014)
The field of infertility research and practice is one of continuous innovation and change, but alongside the increasing sophistication of assisted reproductive techniques there is as strong a need as ever for clinical experience and expertise and common practical sense to inform diagnosis and clinical decision making. Now in its fourth edition, Infertility in Practice is practical and gives the clinician a clear picture of the aetiology of infertility and a careful assessment of the basis for treatment options. A thoroughly comprehensive book that provides sound theory and evidence based therapy, this book is a must for any practitioner dealing with infertility.